METAMORPHOSIS AND THE ARCHETYPAL WOMAN: MORALITY AND MYTH IN THE TALE OF TSUIPU AND KHAULIPU - Swu, Tokali (International Journal of Research -GRANTHAALAYAH, 2025)
This paper seeks to explore the Sumi Naga Folktale “Tsuipu and Khaulipu” from the perspective of gender, morality and mythic transformation. Examining on the main characters, Tsuipu, Khaulipu (the fairy wife) and Muchupili (the witch), the narrative highlights cultural norms around feminity, beauty, betrayal, loyalty and supernatural justice. The tale conveys cultural values, drawing on the themes of renewal, metamorphosis, and sacred feminity to examine and reinforce the Sumi community norms. Exploring cyclical patterns, through the character of Khaulipu and contrasting her with the envious witch Muchupili, the study explores the symbolic meaning and moral principles inherent in traditional indigenous narratives. As the tale unfolds in a mystical realm ,it shows a series of transformative events, featuring magical shifting, renewal and rebirth, exemplified by a fairy who turned into ‘Aghugha lho’(Waxen Figure), trees growing from her grave and a wife returning through the fruit of a tree. These motifs symbolise moral consequences, feminine endurance and cyclical renewal, giving the narrative deeper meaning. The tale critiques moral shortcomings, highlighting how disobedience and misunderstandings can lead to loss and tragedy through the character of Tsuipu. Ultimately the tale reveals the transformative and redemptive power of the feminine, restoring balance through its true nature. This paper based on folklore studies and gender theory, examines how myths transmit social values, gender roles and ancestral belief system, arguing that the myth functions as a cultural narrative where feminine power is both celebrated and circumscribed, mystified through transformative processes.